Analysis of Dose Distribution Alpha and Secondary Particles in Therapy Alpha for Glioblastoma Cancer Using MCNP6 Software - Agustina, Sheila; Suharyana, Suharyana; Kusumandari, Kusumandari; Arianto, Fajar (Diponegoro University Semarang Indonesia, 2025)
The alpha therapy modeling was performed for the treatment of glioblastoma brain cancer using MCNP6 software. The simulation used a head and neck phantom geometry, with a spherical shape of the radiation direction of the cancer cells with a radius of one cm divided into 27 targets. One radiation source is directed to each target center of the cancer cells with five energy variations, namely (430, 425, 415, 410, and 400) MeV. The simulation results are in the form of a distribution of absorbed doses in all targets and healthy cells around them. The simulation results show an average dose distribution of (1.2902 ± 0.0024) 10-11 Gy/alpha with an isodose level of 69.75%. The healthy organ that receives the largest dose and secondary particle distribution after cancer cells is the brain, with an accumulative dose of (1.7446 ± 0.0033) 10-15 Gy/alpha. The dose distribution on cancer cells shows that the irradiation time to kill glioblastoma cancer cells is (1456±0.14) seconds with an alpha current of 1 nA.